Liquid silicone embolism syndrome (SES) in lungs and liver – A case report. (August 2021) - Nebel, Annika; Veit, Florian; Weber, Anne; Martz, Walter; Lasczkowski, Gabriele; Dettmeyer, Reinhard
Highlights: Liquid silicone embolism in lungs and liver after silicone injection into genitals. Accumulation of mainly small silicone oligomers in lungs and liver. Larger silicone oligomers remain at site of injection. Numerous vacuoles in the liver due to repeated silicone oil embolism. Abstract: Silicone embolism syndrome (SES) is a well known complication after injection of silicone gel as well as liquid silicone. Rarely, men use physiologic salt solution or liquid silicone injected into the subcutaneous tissue of the scrotum, the penis, the upper genital or the inguinal region. Those men, who call themselves "siliconers", want to get a larger penis and scrotum, also visible when wearing clothes. Injections of liquid silicone in the mentioned regions can lead to liquid silicone embolism in the lungs and also the liver, sometimes eventually leading to death via right heart failure as in the present case. Autopsy revealed "frog spawn"-like vacuoles in the subcutaneous tissue of the genital region and liquid silicone embolism in lungs and liver. Additionally, toxicological analyses revealed different liquid silicones. Smaller oligomers were transported into lung and liver, larger ones showed local enrichment at the injection site. The seized Polydimethylsiloxane (PDMS) could not be detected in abdominal fat, blood or urine, potentially due to low perfusion of fat tissue, the aqueous character of blood and urine or the time span between last injection and death.